Análise do programa saúde na escola do município de Fortaleza - Paiva, Georgia Medeiros (Universidade de Fortaleza, 2012)
Made available in DSpace on 2019-03-29T23:43:41Z (GMT). No. of bitstreams: 0 Previous issue date: 2012-12-18 === The School Health Program (PSE) established in Brazil in 2007, is an intersectoral policy between the Ministries of Health and Education with the aim of contributing to the education of students within the public basic education and / or of primary health care through health promotion, prevention and health care. This study aims to understand the general perception of regional municipal technicians and technical sectors of Education and Health on the implementation of the School Health Program, in Fortaleza, Ceará. Specific objectives aim to identify strategies for implementing the program; describe the contribution of the sectors of education and health, examining the facilitators, barriers and challenges associated with implementing the program. This is an exploratory, descriptive qualitative approach, in which we used the technique of semi-structured interviews with municipal technicians of health and education and focus groups with the technical regional district health and education, conducted in six executive secretariats of the regional municipality of Fortaleza-Ceará. We analyze the results of the light Content Analysis defended by Bardin (2008), categorizing the lines under four themes central constituent of interpretative network, such as: 1) Implementation of School Health Program, 2) Relevance of the Program for the City; 3) Involvement to work together sectors of health and education in the program, 4) Relationship of institutional spheres (x Health Education). The results show that the PSE developed in the city needs to be strengthened as intersectoral actions, which seek to contribute to a critical reflection on the process of implementation of the program with regard to the relationship between the sectors of health and education. The study points to the need to rethink and dynamics of these processes to strengthen intersectoral actions in a more coordinated and sustainable, enabling the creation of regular meetings with agendas and systematic; foster socialization spaces of the proposed PSE to other sectors; propose a regional shows with program activities; create indicators that can evaluate the program and to improve communication between the Intersectoral Working Group, thus having a greater monitoring of activities in the region. === O Programa Saúde na Escola (PSE), instituído no Brasil em 2007, é uma política intersetorial entre os Ministérios da Saúde e da Educação com o objetivo de contribuir para a formação integral dos estudantes, no âmbito da rede pública de Educação Básica e/ou das unidades básicas de saúde, por meio de ações de promoção, prevenção e assistência à saúde. Este estudo tem como objetivo geral compreender a percepção dos técnicos municipais e técnicos regionais dos setores de Educação e da Saúde sobre a implantação do Programa Saúde da Escola, no município de Fortaleza-Ceará. Como objetivos específicos pretendemos identificar as estratégias de implantação do programa; descrever a contribuição dos setores de educação e de saúde, analisar os aspectos facilitadores, os obstáculos e os desafios associados à implantação do programa. Trata-se de um estudo exploratório, descritivo de abordagem qualitativa, no qual fizemos uso da técnica de entrevistas semiestruturadas com técnicos municipais da área da saúde e educação e de grupos focais com os técnicos regionais dos distritos de saúde e de educação, realizado nas seis secretarias executivas regionais do município de Fortaleza-Ceará. Analisamos os resultados a luz da Análise de Conteúdo defendida por Bardin (2008), categorizando as falas em quatro eixos temáticos centrais constitutivos da rede interpretativa, tais como: 1) Implantação do Programa Saúde na Escola; 2) Relevância do Programa para o Município; 3) Envolvimento para se trabalhar em conjunto os setores de Saúde e Educação no programa; 4) Relação das esferas institucionais (Educação x Saúde). Os resultados demonstram que o PSE desenvolvido no município precisa ser fortalecido como ações intersetoriais, as quais buscam contribuir para uma a reflexão crítica sobre o processo de implantação do programa, no que se refere à articulação entre os setores da Saúde e da Educação. O estudo aponta para a necessidade de se repensar dinâmicas e processos para o fortalecimento dessas ações intersetoriais, de forma mais articulada e sustentável; viabilizar a criação de agendas com reuniões periódicas e sistemáticas; fomentar espaços de socialização da proposta do PSE para os demais setores; propor uma mostra regional com atividades do programa; criar indicadores que possam avaliar o programa e melhorar a comunicação entre o Grupo de Trabalho Intersetorial, havendo assim um maior acompanhamento das atividades nas regionais.